2022
DOI: 10.1039/d2ra07386b
|View full text |Cite
|
Sign up to set email alerts
|

External environment sensitive circularly polarized luminescence properties of a chiral boron difluoride complex

Abstract: Circularly polarized luminescence properties of chiral boron difluoride complexes bearing a diethylamino group successfully controlled by external environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 93 publications
(36 reference statements)
0
6
0
Order By: Relevance
“…In all complexes, the boron centre took a tetrahedral conformation, which is similar to results in previous reports. 18,19…”
Section: Synthesis Structures and Thermal Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In all complexes, the boron centre took a tetrahedral conformation, which is similar to results in previous reports. 18,19…”
Section: Synthesis Structures and Thermal Propertiesmentioning
confidence: 99%
“…As part of our research for the creation of highly fluorescent materials, we recently reported that mono- 14,18,19 and dinuclear 20 boron difluoride complexes exhibited efficient photoluminescence even in the aggregated state. Furthermore, we have achieved lowering the melting point of a boron difluoride complex by introducing polyethylene glycol (PEG) chains into the aromatic rings of Schiff-base ligands, and have succeeded in demonstrating CPL in the solvent-free liquid state.…”
Section: Introductionmentioning
confidence: 99%
“…Small organic CPL‐active molecules (CPL‐SOMs) have attracted considerable attention in the last decade for their potential application in next‐generation optical devices. Our group is investigating CPL‐SOMs with chiral Schiff‐base ligands, and recently reported that boron difluoride complexes exhibit efficient and tunable CPL properties [1, 2] . These findings prompted us to clarify two questions: (1) How do the molecular structures affect the CPL properties; (2) How does molecular alignment affect their CPL properties.…”
Section: What Prompted You To Investigate This Topic/problem?mentioning
confidence: 99%
“…Our group is investigating CPL-SOMs with chiral Schiff-base ligands, and recently reported that boron difluoride complexes exhibit efficient and tunable CPL properties. [1,2] These findings prompted us to clarify two questions: (1) How do the molecular structures affect the CPL properties; (2) How does molecular alignment affect their CPL properties. The second of these questions is discussed in this work.…”
mentioning
confidence: 99%
“…As part of our research to create efficient CPL-active materials, we have been investigating boron difluoride complexes with (N O)-chelate Schiff-base ligands. [17][18][19][20] In the course of these studies, we have achieved the development of materials that exhibit highly efficient CPL in response to molecular aggregation [17,19,20] or changes in the external environment [18] through the appropriate design of the Schiffbase ligands. In this work, we designed the new helical boron complexes 1 a and 1 b based on Schiff-base [4]helicene ligands (Figure 1).…”
Section: Introductionmentioning
confidence: 99%